Clinical features and outcomes of retroperitoneal unicentric Castleman disease resected as sarcomas: insights from a high-volume sarcoma center - Gao, Haicheng; Li, Wenjie; Zou, Boyuan; Liu, Shibo; Miao, Chengli (Frontiers in Surgery, 2024)
BackgroundCastleman disease (CD) is a rare lymphoproliferative disorder that can occur anywhere along the lymphatic pathway. Retroperitoneal unicentric Castleman disease (UCD) is an extremely rare manifestation. This study aims to explore the clinical features and surgical treatment of retroperitoneal UCD.MethodsWe retrospectively reviewed patients who underwent retroperitoneal tumor surgery and were diagnosed with CD based on postoperative pathology before December 31, 2022. Data from these patients were collected and analyzed.ResultsA total of 15 patients were included in the final analysis. All patients underwent radical resection under general anesthesia. Two out of 15 patients (13.3%) experienced serious complications but recovered well. There were no perioperative deaths. The median follow-up time was 78.5 months (range: 18–107.5 months), and no deaths or recurrences occurred during this period.ConclusionsSurgical treatment for retroperitoneal UCD is safe. Patients with retroperitoneal UCD can achieve long-time survival through complete resection.